Epidemiological profile of mortality in an emergency service in the Federal District - Miranda, Luanne (2022)
Introduction: the population's way of life and life expectancy has changed and transformed the profile of illness and mortality. Research into the causes of death allows us to know a society. By evaluating the level and pattern of mortality, it is possible to analyze the social and economic conditions and what their political and social needs are. Objective: to survey the epidemiological profile of morbidity and mortality in an emergency service. Methods: descriptive, cross-sectional and quantitative study, with data categorized according to the ICD-10 death tabulation list, statistically analyzed. Results: 459 deaths, 58.6% male, mean age 67.8 years, with outcome mainly in the emergency room, during the night and dawn. The chapter on respiratory diseases represented the most incidence in the multiple causes of death. Deaths from firearms and falls represented the highest rate of necropsy requests. Conclusion: The knowledge of sociodemographic and clinical data reflects the degree of quality of life and health care offered, constituting a necessary strategy to assess the effectiveness of the health system, allowing the government to assist in the creation of new public health policies.